Simple Double Object Constructions in Igbo: A Minimalist Approach (2018)
Double object constructions provide interesting evidence about the valency of verbs, agreement relations and word order variation across languages. However, existing studies have not paid adequate attention to investigating how the case feature of the objects are valued in Igbo double object constructions and how they are derived in phases based on the split projection hypothesis. This study, therefore, analyses double object constructions in Igbo with a view to determining how the case feature of the internal arguments are valued as well as the derivational procedure based on the phase model of the Minimalist Program. The study observed that the shells for simple DOCs were uP-AppIP- VP. The light u values the case feature of the indirect object; the applicative head introduces the IO and also values the case feature of the direct object while the lexical verb assigns (l-role to the indirect object. In the derivation of the simple double object constructions uP and ApplP are phases.